RANCANG BANGUN MINI REAKTOR DAN UJI REAKTOR PADA PERENGKAHAN KATALITIK LEMAK SAPI MENJADI BAHAN BAKAR CAIR MENGGUNAKAN KATALIS MgO DAN ZEOLIT - Adi Riyadhi; Syahrullah Syahrullah (Integrated Lab Journal, 2018)
Animal fats such as beef fat/tallow widely available on the market and relatively cheap. Public awareness is high enough the importance of health by reducing the consumption of fatty foods, making animal fat is not utilized to the maximum, so the research was about catalytic cracking beef fat/tallow into liquid fuels with the opened reactor  using a  nature zeolite and MgO as catalyst. The colour of liquid that produced by the opened reactor and using natural zeolite catalyst was clear yellow liquid oils with the composition of the carbon chain were C12- C20. The results of GC - MS analysis showed that the composition of the group of compounds were 64.51% of alkanes, 27.37% of alkenes, 0.7% of aldehyde, 4.34% of ketone and 3.08% of fatty acids. The colour of liquid that produced by the opened reactor and using MgO catalyst was brownish yellow liquid oils. The results of GC-MS analysis showed that the composition of the carbon chain were 17.85% of C7-C11 and 82.15 % of C12-C19. The results of GC-MS analysis showed that the composition of the group of compounds were 57.6% of alkanes, 32.16% of alkenes and 10.24% of ketones. The composition of the cracking results tallow oil compounds using natural zeolite catalysts showed that the oil can be used as a diesel, while using MgO catalyst generated 17.85 % of liquid fuels equivalent of petrol and 82.15 % liquid fuels equivalent diesel.